2014
DOI: 10.1093/trstmh/tru055
|View full text |Cite
|
Sign up to set email alerts
|

The effects of season and meteorology on human mortality in tropical climates: a systematic review

Abstract: Research in the field of atmospheric science and epidemiology has long recognized the health effects of seasonal and meteorological conditions. However, little scientific knowledge exists to date about the impacts of atmospheric parameters on human mortality in tropical regions. Working within the scope of this systematic review, this investigation conducted a literature search using different databases; original research articles were chosen according to pre-defined inclusion and exclusion criteria. Both seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 89 publications
0
40
0
5
Order By: Relevance
“…A huge amount of evidence has pointed to the relationship between daily variations in meteorological parameters and mortality [2]. The research conducted in Serbia has also shown heat-related mortality, especially among elderly females and Roma population [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A huge amount of evidence has pointed to the relationship between daily variations in meteorological parameters and mortality [2]. The research conducted in Serbia has also shown heat-related mortality, especially among elderly females and Roma population [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of several studies from Africa demonstrated that rainy season was associated with higher all‐cause child mortality. This was observed in the Gambia, Senegal, Ghana, Nigeria, Kenya, Tanzania and Burkina Faso .…”
Section: Discussionmentioning
confidence: 76%
“…Different studies have collected data on the relationship between the urban heat island, its associated thermal conditions, and mortality in Asian and Australian cities. The conclusion is that the mortality rate could be exacerbated by the UHI phenomenon [23,24]. An almost linear relationship between UHI intensity and excess mortality rate was demonstrated through a study of 30 years of data in Shanghai [3].…”
Section: Introductionmentioning
confidence: 94%